Meio Ambiente e Agricultura: Impactos Econômicos da Adequação ao Código Florestal Brasileiro - Raquel Breitenbach (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
How historically sought the development in Brazil caused problems in the economic, environmental and social, thanks to its central focus on economic growth. Highlight the urgent imperative of environmental protection, and compliance and adequacy of laws – and a more sustainable agriculture – have a unique role in this process. The objective of this task in identifying and assessing the economic impacts of compliance with the Brazilian Forest Code (CFB), in particular the items relating to the Permanent Preservation Area (APP) and Legal Reserves (RL) on farms in the northern region of Rio Grande do Sul. To conduct the survey, were intentionally selected ten representative family production units in the region, which passed on economic, environmental data and allowed the visitation on the property. These PSUs were raised economic and financial data as well as environmental aspects, apart from being gone all the territory of the property to analyze the initiative's conformity with the CFB. As a result, it was found that all the properties analyzed need to make adjustments to the CFB, therefore, will decrease in Agricultural Income (RA) Annual. The greatest reduction was observed in the Property 5, which would be R $ 30,225.12 and the lowest reduction of RA was the Property 8, R $ 1,441.61.